23 The Role of AMPK and PKCε in the Attenuation of ET-1 Induced Cardiomyocyte Hypertrophy by RIC Human Serum. (19th January 2014) - Vanezis, A P; Butt, M; Samani, N J; Rodrigo, G C
Abstract : Rationale: We have previously shown that serum from healthy volunteers who have undergone Remote Ischaemic Conditioning (RIC) reduces hypertrophy in rat cardiomyoblasts. Here we investigated the roles of AMPK and PKCε in this process. Methodology Blood was taken from healthy volunteers after 3 cycles of 5 min of upper arm cuff inflation/deflation and the serum applied to H9c2 cardiomyoblasts in culture. Cells were treated with endothelin-1 (ET-1) to stimulate hypertrophy, and cell area determined using immunofluorescence at 48 h. The role of AMPK-signalling in the anti-hypertrophic effect of RIC-serum was probed using the AMPK inhibitor compound-C and AMPK phosphorylation and PKCε translocation were analysed using Western blots. Results ET-1 increased cell surface area by >45% from 1.47 x 104 ± 0.08 μm 2 in control cells to 2.14 x 104 ± 0.09 μm 2 in ET-1 treated cells (n = 8, >1000 cells per treatment, p < 0.001). This hypertrophic effect was reduced by pre-treatment with RIC-serum (1.63 x 104 ± 0.09 μm 2 (p < 0.01) and by activation of AMPK with AICAR (1 mM) (1.52 ± 0.03 μm 2 (p < 0.001). Moreover, the anti-hypertrophic effect of RIC-serum was blocked by compound-C (10 μM) (1.93 ± 0.1 μm 2 ; ns). RIC-serum caused a transient translocation of PKCε after 30 min (76.3%), which dissipated after 48 h to be replaced by a significant increase in cytosolic PKCε (3.4 ± 0.5 fold, p < 0.02). RIC-serum led to an increase in phosphorylation of AMPK after 30 min of 4.7 ± 2.1-fold, compared to unconditioned serum, which was blocked by compound-C (1.6 ± 0.7 fold). Conclusion: Our data suggests that PKCε and AMPK-signalling are involved in the anti-hypertrophic action of RIC-serum.